Stroke patterns of sprint and distance swimmers
Sixteen high-level performers were analyzed swimming crawlstroke at different speeds. No differences in either the patterns of movement or the biomechanical factors were revealed. The most important aspect of stroking is how much of the total force is actually used to propel the swimmer through the water ("effective" force or "propelling" efficiency). Faster swimmers have a greater effective force over a longer period of the pull. Hand angle and hand velocity are the two most important contributors to peak force. Some swimmers were observed to have two peaks of force during a pull while others had one. The most common reason for two peaks was the change of hand position that occurred between the insweep and extension to initiate the finish phase. [This action is sometimes called a transition phase and for a moment effective force is lost. It usually results from the first part of the pull being too deep. A rapid change to place the hand and arm in a more effective position to execute extension is required. During that change the hand slips to the more effective position.] The unimodal swimmer is able to continue the emphasis of the insweep through the transition to the finish of the stroke, maintaining effective force all the time. The basis of an effective pull is accelerating, although not dramatically, the hand/forearm combination throughout the total pull. Implication: Although top-level swimmers were shown to produce both one and two-peak force curves, it would seem to be mechanically more efficient to attempt a one peak pull. That can be achieved by gradually accelerating the pull from the inception of the insweep through to the finish.